Pathogenesis of Wilson disease - Scheiber, Ivo Florin; Brůha, Radan; Dušek, Petr (Handbook of clinical neurology, 2017)
Wilson disease is an autosomal-recessive disorder originating from a genetic defect in the copper-transporting ATPase ATP7B that is required for biliary copper secretion and loading of ceruloplasmin with copper. Impaired ATP7B function in Wilson disease results in excessive accumulation of copper in liver, brain, and other tissues. Toxic copper deposits may induce oxidative stress, modify expression of genes, directly inhibit proteins, and impair mitochondrial function, leading to hepatic, neuropsychiatric, renal, musculoskeletal, and other symptoms. Hepatocyte dysfunction initially manifests as steatosis and later may progress to other hepatic phenotypes such as acute liver failure, hepatitis, and fibrosis. In the brain, copper accumulates in astrocytes, leading to impairment of the blood-brain barrier and consequent damage to neurons and oligodendrocytes. Basal ganglia and brainstem are the brain regions with highest susceptibility to copper toxicity and their lesions lead to various combinations of movement and psychiatric disorders. This chapter will give an overview of the essential requirement of copper for biologic processes and the molecular mechanisms employed by cells to maintain their copper levels in a proper range. We will specify the physiologic functions of ATP7B and the consequences of its dysfunction and summarize the current knowledge on the pathogenesis of liver and neuropsychiatric disease. Finally, we will describe the consequences of copper overload in Wilson disease in other tissues.
Keywords: mozek; Humans; Copper; hematoencefalická bariéra; Hepatolenticular Degeneration; Blood-Brain Barrier; Copper-Transporting ATPases; lidé; ATPasy transportující měď; měď; duševní poruchy; liver fibrosis; copper; Brain; Wilson disease; Mental Disorders; neurodegeneration; ATP7B; hepatolentikulární degenerace